STRATEGY OF SUSTAINABLE BUSINESS DEVELOPMENT BASED ON COMMUNITY (STUDY OF TODAY'S MODERN COFFEE SHOP BUSINESS ACTORS) - Yussi Ramawati; Harmiaty Bahar; Muh. Husriadi (Nomico, 2024)
This study explores the sustainable community-based business approach adopted by modern coffee shops in Kendari City to boost community participation and foster customer loyalty. Through qualitative research, including case studies and in-depth interviews with business owners, employees, and community members, the findings indicate that involving the community in innovation and business adaptation strengthens customer relationships and enhances business sustainability. By engaging the community, coffee shops are able to create a sense of ownership, resulting in higher customer retention and greater brand loyalty. The approach also proves effective in addressing operational challenges such as fluctuating demand and supply disruptions by leveraging community-driven solutions. Furthermore, the adoption of sustainable practices, such as sourcing local ingredients, minimizing waste, and utilizing eco-friendly packaging, increases operational resilience and attracts environmentally conscious customers. This business model aligns with local policies promoting the sustainability of MSMEs and offers a replicable framework for other small businesses in similar contexts. Ultimately, the combination of community engagement and sustainable practices not only generates economic benefits but also builds social capital, ensuring long-term business resilience and contributing to local economic growth.